2021
DOI: 10.1002/cphc.202100542
|View full text |Cite
|
Sign up to set email alerts
|

Early Divergence in Misfolding Pathways of Amyloid‐Beta Peptides

Abstract: The amyloid cascade hypothesis proposes that amyloid‐beta (Aβ) aggregation is the initial triggering event in Alzheimer's disease. Here, we utilize NMR spectroscopy and monitor the structural dynamics of two variants of Aβ, Aβ40 and Aβ42, as a function of temperature. Despite having identical amino acid sequence except for the two additional C‐terminal residues, Aβ42 has higher aggregation propensity than Aβ40. As revealed by the NMR data on dynamics, including backbone chemical shifts, intra‐methyl cross‐corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Dynamic studies of IDPs at higher temperatures may be made possible through a shift to acidic pH where amide‐water exchange is effectively quenched, or preferably, through switching to non‐exchangeable nuclear spins such as 13 C. In this regard, we note that the newly developed singlet‐filtered NMR experiments allow the study of the relaxation of non‐exchangeable Hα protons of glycines in IDPs [21] . In addition, the singlet relaxation times of glycines provide novel sensitive probes of motions in IDPs applicable at high temperatures [22] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic studies of IDPs at higher temperatures may be made possible through a shift to acidic pH where amide‐water exchange is effectively quenched, or preferably, through switching to non‐exchangeable nuclear spins such as 13 C. In this regard, we note that the newly developed singlet‐filtered NMR experiments allow the study of the relaxation of non‐exchangeable Hα protons of glycines in IDPs [21] . In addition, the singlet relaxation times of glycines provide novel sensitive probes of motions in IDPs applicable at high temperatures [22] …”
Section: Resultsmentioning
confidence: 99%
“…[21] In addition, the singlet relaxation times of glycines provide novel sensitive probes of motions in IDPs applicable at high temperatures. [22]…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Due to their exchange symmetry property, singlet-states are protected from several relaxation mechanisms and could therefore possess lifetimes longer than the magnetization relaxation time T 1 , hence called long-lived states 42 . The glycine-based singlet-state relaxation time ( T s ) is however sensitive to the dynamics of glycine residues at pico-to-nanoseconds timescale and it has recently been demonstrated that the T s / T 1 ratio is a sensitive probe of peptide dynamics in the “intermediate” motional regime where rotational correlation time ( τ c ) is around 1/ω H (at proton Larmor frequency of 600 MHz, it is ~265 ps) and the T s and T 1 relaxation times move in opposite directions in response to dynamical alterations in τ c 43 45 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…1 ), several glycine residues exhibited almost the same singlet-state and longitudinal relaxation times T s and T 1 in the condensed phase as in the dilute solution. Importantly, the opposite temperature-dependence of T s and T 1 suggested that the motions of glycine residues occurred at intermediate timescales close to T 1 minimum where the sensitivity of T s / T 1 ratio to dynamical changes is maximal 43 45 . Accordingly, the indistinguishable T s / T 1 ratios in dilute solution and condensed phases strongly suggest that glycine residues of clp preserve their large local dynamics inside polyU-induced droplets.…”
Section: Discussionmentioning
confidence: 99%
“…These include (i) inhibition of the transformation of PAP248-286 monomers into amyloids, iii) hindering of the cleavage of the PAP248-286 peptide from the PAP protein, iii) perturbation of the structure of the SEVI fibrils, and iv) neutralization of the overall charge of the SEVI fibrils. Out of the above-mentioned approaches, inhibition of early stages of misfolding of PAP248-286 monomers could be very promising, as it has been reported to similar amyloidogenic peptides that are related to Alzheimer’s and Parkinson’s diseases [13] , [14] . While the biological activity of PAP248-286 is mostly reported to its aggregated amyloid form, studies have shown that the monomeric form of PAP248-286 is also biologically active [6] , [15] .…”
Section: Introductionmentioning
confidence: 99%